Love as radical politics - Hayes, Grahame (PINS-Psychology in Society, 2017)
With the “affective turn” in social studies, the discussion of the role of emotions in social and political life is increasingly becoming a valid topic of inquiry. However, it is the “negative” emotions, like fear, anger, shame, that tend to dominate the discussions, with less attention being given to discussions of hope, compassion, and love. Srecko Horvat’s The radicality of love is an attempt to correct this bias. His text makes a case for the social importance of love in the reinvention of revolutionary politics. He does this through a discussion of some of the revolutions of the twentieth century, as well as some of the (revolutionary) social movements of the twenty first century.